National Guard Special Forces Enhancing the Contributions of Reserve Component Army Special Operations Forces - Peters, John E. (RAND Corporation, 2012)
U.S. Army Special Operations Command sought options for enhancing the contributions of the Special Forces Groups of the U.S. Army National Guard (ARNG). The research was motivated by the sponsor's belief that ARNG might occupy high-value capability niches that could be put to use in future deployments. This study analyzed ARNG Special Forces capabilities as well as the legal and policy guidance that governs ARNG's functioning.